Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Solve. -6 = 14 - z/3Subtract 14 from both sides
-20 = -z/3
Multiply -3 by both sides to get rid of the negative and 3 with the z.
z= 60
-20 = -z/3
Multiply -3 by both sides to get rid of the negative and 3 with the z.
z= 60
−6=14−z3
Step 1: Simplify both sides of the equation.−6=14−z3
Simplify: −6=−13z+14
Step 2: Flip the equation.−13z+14=−6
Step 3: Subtract 14 from both sides.−13z+14−14=−6−14−13z=−20
Step 4: Multiply both sides by 3/(-1).(3−1)*(−13z)=(3−1)*(−20)z=60
Answer:z=60
Step 1: Simplify both sides of the equation.−6=14−z3
Simplify: −6=−13z+14
Step 2: Flip the equation.−13z+14=−6
Step 3: Subtract 14 from both sides.−13z+14−14=−6−14−13z=−20
Step 4: Multiply both sides by 3/(-1).(3−1)*(−13z)=(3−1)*(−20)z=60
Answer:z=60
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.